Recent advances and clinical insights into the use of proteomics in the study of atherosclerosis. (3rd August 2017) - Mourino-Alvarez, Laura; Baldan-Martin, Montserrat; Rincon, Raul; Martin-Rojas, Tatiana; Corbacho-Alonso, Nerea; Sastre-Oliva, Tamara; Barderas, Maria G.
ABSTRACT: Introduction : The application of new proteomics methods may help to identify new diagnostic/predictive molecular markers in an attempt to improve the clinical management of atherosclerosis. Areas covered : Technological advances in proteomics have enhanced its sensitivity and multiplexing capacity, as well as the possibility of studying protein interactions and tissue structure. These advances will help us better understand the molecular mechanisms at play in atherosclerosis as a biological system. Moreover, this should help identify new predictive/diagnostic biomarkers and therapeutic targets that may facilitate effective risk stratification and early diagnosis, with the ensuing rapid implementation of treatment. This review provides a comprehensive overview of the novel methods in proteomics, including state-of-the-art techniques, novel biological samples and applications for the study of atherosclerosis. Expert commentary : Collaboration between clinicians and researchers is crucial to further validate and introduce new molecular markers to manage atherosclerosis that are identified using the most up to date proteomic approaches.